PENINGKATAN KESADARAN SEJARAH SISWA MELALUI PEMANFAATAN SUMBER ISU KONTROVERSIAL PADA MATA PELAJARAN IPS DI SMP NEGERI 4 PALU - Sulhan, Sulhan (Katalogis, 2016)
This research aims to: 1) analyze the utilization of controversial issue learning source in social learning of SMP Negeri 4 Palu; and 2) analyze the students’ history awareness improvement through controversial issue learning source in social learning of SMP Negeri 4 Palu. The method employed was quantitative with data collection covered interview, observation, documentation and questionnaire. The data were analyzed by using qualitative technique from Miles and Huberman interactive model. The result and conclusion were as follow: social subject teacher has already utilized learning source such as school environment, books, especially textbooks. Controversial issue happen frequently causing pro and contra that history contented material, like the entry of religion and its development and Islam culture in archipelago and other events around proclamation and its preparation. The utilization of learning source on controversial issue has increased students’ history awareness in good category. Substantial reference indicates that students’ history awareness increased to 30 indicators which were classified into 4 main aspects, namely: discipline, communication, psychology and routine. Discipline and communication were evaluated good enough whereas psychology and routine were categorized good. Viewed from technical aspect or the place of the occurrence of students’ history awareness, it can be divided into 2 parts, namely: learning process and supporting facility of learning (learning source). From the learning process, it can be concluded that it already run well except Indonesian map is nothing. If history awareness is viewed from outside class, then, it concluded there is an indication of history awareness particularly when ceremony commencement and do not throw the garbage improperly.